The Relation between Reading Habit and Vocabulary Size of Seventh Semester English Department Students of Mulawarman University - Rizal Nor Wahit; Maria Theodora Ping; Bibit Suhatmady (English Department, Faculty of Teacher Training and Education, Mulawarman University, 2019)
The purposes of the study were: (1) To find out seventh semester English Department students’ reading habit. (2) To find out seventh semester English Department students’ vocabulary size. (3) To find out the relationship between students’ reading habit and vocabulary size. The design of this study was correlational research design using quantitative approach. The population of this study was the seventh semester English Department students of Mulawarman University in the Academic Year 2018/2019 with the total sample of 50 students. The instruments used for the study were Reading Habit Questionnaire and Vocabulary Size Test. The time for collecting the data was different for each instrument in order to avoid errors or undesired results. Then, the researcher correlated the data using Pearson Product Moment Correlation formula in SPSS. This study showed three findings. First, it was found that the mean score of the reading habit questionnaire was 49.7, meaning that the students’ reading habit was classified as moderate. Second, it was found that the mean score of the vocabulary size test was 7968, meaning that the students’ vocabulary size fell in the category of Mid-Frequency level. Third, after analyzing the data using Pearson Product Moment formula, the researcher found that reading habit and vocabulary size had a positive, yet “very low” correlation (with rcomputed = 0.188). Having positive “very low” correlation means that both the variables had the tendency of getting similar results, but then the tendency was weak. In other words, this means that students who got high score in their reading habit did not automatically get high score in the vocabulary size test, and vice versa. However, there might be some factors affecting the findings of the study. Therefore, further investigation on which other factors might affect reading habit and its relation with vocabulary size should be done in the future.